Determination of caffeine at unmodified carbon paste electrode - Stočes, Matěj; Kosová, Lucie; Švancara, Ivan (University of Pardubice, 2013)
In this paper, electrochemical and electroanalytical characterization of caffeine has been carried out, for the first time, with unmodified carbon paste electrode and in combination with cyclic voltammetry and square-wave voltammetry as the measuring techniques of choice. After defining the proper conditions for the electrode oxidation in highly acidic media and setting the key experimental parameters accordingly, a simple method was subsequently tested on model analyses of real samples (energy and Cola drinks).